Study og Engine Performance when Using Ethanol as Blended Fuel For Spark Ignition Engine - Mohd Azra'in Zainuddin, Mohd Azra'in (Universiti Teknologi Petronas, 2009)
The energy crisis created an incentive to study and evaluate alcohols as an alternative fuel in spark-ignition engines. Since energy resources are limited, energy conservation and its efficient use has become a major option. In those days of plentiful gasoline, concerns about dependence on crude oil did not exist. Interest in the ability of a vehicle to consume a fuel other than gasoline was encouraged by a desire for energy independence and convenience. This project investigates the effect of using ethanol-gasoline blends on spark ignition engine performance. The engine parameters that have been focused in this study are the fuel consumption, engine’s torque and power produced. There are many other engine parameters that can be studied to measure the engine performance but it is not convenient to investigate all of them due to the given duration for this project. The other engine parameters are such as the equivalence air–fuel ratio, volumetric efficiency, brake thermal efficiency, brake specific fuel consumption, and exhaust emissions (CO, CO2 and HC). Some of these engine parameters will be discussed literally in conducting this project. A single cylinder spark ignition engine will be used for conducting this study. Engine performance tests will be conducted for fuel consumption, engine torque and power produced, using unleaded gasoline–ethanol blends with different percentages of fuel at three-fourth throttle opening position and variable engine speed ranging from 1000 to 3500 rpm with increment of 500 rpm. From the literature studies, the results showed that blending gasoline with ethanol increases the fuel consumption, brake torque and brake power. After all, the optimum ethanol-blend percentage is to be determined from the 6 fuel blends used in the experiment, which are E-0, E-5, E-10, E-15, E-20 and E-85.